Demand Chain Management : Supply Chain Management + Orientasi Pasar - Mulyono, Fransisca (Business Administration Study Program - Universitas Katolik Parahyangan, 2011)
In 1980s and 1990s decades supply chain is a popular term implemented in manybusiness firms in the world because of its capability to increasing operational costefficiency which lead to cheaper product price. In that time it is widely believed thatlower product price will yield the higher return in companiesâs profit, even in the longterm.As time goes by, itâs grandeur become clearly faded : in the long term com-panies facing more loss because supply chain do not have a market orientation,an orientation that can keep companies stay in market for a long time and higherprofit. As a consequences, in early 2000s there is another new term appeared : de-mand chain management. This term actually is a combination of supply chain andmarket orientation term. Zara, an small apparel company compared to world classfashion designer, gaining higher profit than world class fashion designer since it isimplementing demand chain management.Keywords: Supply Chain Management, efficiency, Demand Chain Management,affectivity, market orientation1